Dye Degradation Enhanced by Coupling Electrochemical Process and Heterogeneous Photocatalysis - Santos,Lidiaine M. (2015)
In this study, we evaluated the combination between an electrochemical process, occurring in the dark, and a heterogeneous photocatalytic process for dye degradation, using the azo dye tartrazine as model of oxidizable substrate. TiO2 P25 and an Ag-doped TiO2 were used as photocatalysts in suspensions containing 50 mg L–1 of tartrazine. The best result, 74% of dye mineralization in 120 min of reaction, was obtained using TiO2 P25 as photocatalyst and a current density of 10 mA cm–2 in the electrochemical cell, a value 30% higher than the sum of the results obtained by heterogeneous photocatalysis (44%) and electrochemical oxidation (13%). The use of Ag-doped TiO2 did not result in significant improvement on tartrazine mineralization, due to the aggregation of these nanoparticles. Our results suggest that this process can be an alternative for a complete treatment (discoloration and mineralization) of tartrazine and most likely other azo dyes.